106k views
1 vote
Find the inverse of each function. g(x)=∛(x-2)

Please show the steps. I can show you what I have so far if you want, too.
Just please don't put some Ludacris thing, like "ldsnvlsjdsv" Okay? thankyou :)

User Cwoebker
by
5.1k points

1 Answer

4 votes

Answer:

x=2

Explanation:

g(x)=∛(x-2) -Substitute g(x)=0

0=∛(x-2) -Swap the sides of the equation

∛(x-2)=0

∛(x-2)=0 -Set the radicand equal to 0

x-2=0

x-2=0 -Move the constant to the right hand side and change its sign

x=2

I Hope this helps! If you are good at geometry I really need help. Please let me know! :)))

User Matthew Bedford
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.